2012
DOI: 10.1063/1.4731236
|View full text |Cite
|
Sign up to set email alerts
|

Explicit formulas for noncommutative deformations of ${\mathbb C}{P^N}$CPN and ${\mathbb C}{H^N}$CHN

Abstract: We give explicit expressions of a deformation quantization with separation of variables for CP N and CH N . This quantization method is one of the ways to perform a deformation quantization of Kähler manifolds, which is introduced by Karabegov. Star products are obtained as explicit formulae in all order in the noncommutative parameter. We also give the Fock representations of the noncommutative CP N and CH N .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In [27] explicit expressions of star products of noncomutative CP N and CH N were provided as the deformation quantization with separation of variables. 1 The reason that they were provided is that CP N and CH N are locally symmetric spaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [27] explicit expressions of star products of noncomutative CP N and CH N were provided as the deformation quantization with separation of variables. 1 The reason that they were provided is that CP N and CH N are locally symmetric spaces.…”
Section: Introductionmentioning
confidence: 99%
“…The symmetry makes our problems be simple ones. In [27], star products on general locally symmetric Kähler manifolds are also discussed, but it is not enough to obtain explicit expression of the star products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…,z N ) to Φ(z,z) for convenience. In [22], it is shown that e −Φ/ corresponds to a vacuum projection operator | 0 0| for the noncommutative CP N . We extend this statement for general Kähler manifolds.…”
Section: Lemma 32 (Berezin) For Arbitrary Kähler Manifoldsmentioning
confidence: 99%
“…Example 4 : Fock representation of noncommutative CH N Here, we give an explicit expression of the Fock representation of noncommutative of CH N [22,23]. We choose a Kähler potential satisfies the condition (3.14)…”
Section: Example 2 : Fock Representation Of a Cylindermentioning
confidence: 99%